PENGARUH MODEL PEMBELAJARAN RECIPROCAL TEACHING BERBANTUAN MODUL DESAIN DIDAKTIS TERHADAP PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SMP KELAS VIII (Universitas PGRI Sumatera Barat, 2019)
This research have a main problem is about the low understanding of mathematical concepts of students. This can be seen from the indicator of interpretation, namely when given a matter of concept understanding in the form of a description, the students just answer the question without any description of the steps in doing the questions or identifying the data in the questions. In addition, schools also have not maximized the use of learning media. Looking at these problems, the authors are interested in applying the Reciprocal Teaching model assisted with didactic design modules to increase understanding of mathematical concepts. This type of research is a quasi-experimental (quasi-experimental). The population in this study were all eighth grade students of 7th KOTABUMI SMP Negeri 2018/2019. The taking of sample was done randomly for random class. Data collection techniques are in the form of observations, interviews and question tests of mathematical concept understanding. The testing of data was done by the Lilifors method for normality tests and Barlett's method to test homogeneity. The analysis technique used in this study is the analysis of one-way variant with unequal cells.The testing of this hypothesis uses a one-way variance analysis with unequal cells, with a significant level of 0.05 from the results of the data obtained Fobs = 51.39948 and Ftable = 3.098. Fobs value> Ftable then H0 is rejected. This means that there is the influence of Reciprocal Teaching learning model assisted by the didactic design module to increase understanding of mathematical concepts of students. Based on the results of multiple comparisons it can be concluded that the Reciprocal Teaching learning model assisted with the didactic design module is better than the conventional model, but not better than the Reciprocal Teaching model. Keywords: Reciprocal Teaching, Didactics, Concepts, Modules,